The first clinical case due to AP92 like strain of Crimean-Congo Hemorrhagic Fever virus and a field survey - GARGILI KELEŞ, AYŞEN (BMC, 2009)
Background: Crimean-Congo Hemorrhagic Fever (CCHF) is a fatal infection, but no clinical case due to AP92 strain was reported. We described the first clinical case due to AP92 like CCHFV. Methods: A case infected by a AP92 like CCHFV was detected in Balkanian part of Turkey. Diagnosis was confirmed by RT-PCR and sequencing. A human serologic and tick survey studies were performed in the region, where the case detected. Results: Thirty eight individuals out of 741 were found to be anti CCHFV IgM positive. The attack rate for overall CCHFV was calculated as 5.2%. In univariate analyses, CCHFV IgM positivity was found to be associated with the age (p < 0.001), male gender (p = 0.001), agricultural activity (p = 0.036), and history of tick bite (p = 0.014). In multivariate analysis, older age (OR: 1.03, CI: 1.01-1.05, p < 0.001), male gender were found to be the risk factors (OR: 2.5, CI: 1.15-5.63, p = 0.020) for CCHFV infection. Conclusion: This is the first human case with AP92 like CCHFV infection. Furthermore, this is the first report of AP92 like strain in Turkey. In the region, elderly males carry the highest risk for CCHFV infection.
Keywords: INFECTION; TURKEY